Statistical Practice: Putting Society on Display. (May 2016) - Mair, Michael; Greiffenhagen, Christian; Sharrock, W.W.
As a contribution to current debates on the 'social life of methods', in this article we present an ethnomethodological study of the role of understanding within statistical practice. After reviewing the empirical turn in the methods literature and the challenges to the qualitative-quantitative divide it has given rise to, we argue such case studies are relevant because they enable us to see different ways in which 'methods', here quantitative methods, come to have a social life – by embodying and exhibiting understanding they 'make the social structures of everyday activities observable' (Garfinkel, 1967 : 75), thereby putting society on display. Exhibited understandings rest on distinctive lines of practical social and cultural inquiry – ethnographic 'forays' into the worlds of the producers and users of statistics – which are central to good statistical work but are not themselves quantitative. In highlighting these non-statistical forms of social and cultural inquiry at work in statistical practice, our case study is an addition to understandings of statistics and usefully points to ways in which studies of the social life of methods might be further developed from here.